A Comprehensive Review of Modeling Approaches for Analyzing Mechanical Properties and Fatigue Performance in Magnesium Alloys - Kumar, Raj; Mursaleen, Mohammad; Harmain, GA (International Journal of Integrated Engineering, 2024)
Abstract Magnesium (Mg) alloys have garnered considerable attention across diverse sectors, encompassing aerospace, automotive, and biomedical domains, owing to their advantageous attributes, which include a notably low density (1.7 g/m3), high strength-to-weight ratio, augmented specific stiffness, heightened damping capacity, and exceptional machinability. This paper provides a comprehensive review of the influence of strain amplitude, strain rate, and temperature on the fatigue life of magnesium alloys. The investigation entails a comparative analysis of fatigue life modeling using established models such as Walker’s and Wheeler’s models, employing a synthesis of experimental and analytical methodologies. Furthermore, the monotonic mechanical properties, encompassing tensile strength and yield stress, are elucidated across a wide temperature range from room temperature (RT) to 300°C, alongside a comparative evaluation vis-a-vis other material counterpart. The paper also encapsulates a comprehensive review and tabulation of the limited analytical studies pertaining to magnesium alloys available in the literature.